168 SELENIUM IN COMBINATION WITH PACLITAXEL AND ITS EFFECTS ON PACLITAXEL-INDUCED CORONARY ARTERY ENDOTHELIAL CELL TOXICITY. (1st January 2006) - Smith, J.; Simoni, J.; Roongsritong, C.
Abstract : Background: Restenosis, which occurs commonly following percutaneous intervention with angioplasty or stents, has been significantly reduced with the newer drug eluting stents using paclitaxel or sirolimus. However, little is known about these drugs' effects on human coronary artery endothelial cells (HCAECs), particularly under pro-oxidative conditions such as ischemia or sepsis. The apoptotic effect of paclitaxel has been demonstrated in other studies. Prior blood substitute studies have demonstrated that selenium, an essential enzyme of GSH-Px, is very effective in preventing oxidative damage caused by Hgb radicals. Therefore, we investigated the effects of the potent restenosis reducing agent paclitaxel, with and without selenium, on HCAECs. Methods: HCAECs were incubated with doses of 0 μM, 1 μM, 10 μM, 100 μM of paclitaxel with or without hydrogen peroxide and/or endotoxins (lipopolysacharide) (LPS) and with or without selenium. Cell lines including selenium were incubated with this agent for 1 week prior to addition of other agents. After treatment, oxidative stress was measured using intracellular levels of GSH and lipid peroxidation. Inflammation was evaluated by VCAM-1 expression. Apoptosis was visualized with annexin-V, FITC conjugate, and a propidium-iodide probe. Results: Paclitaxel at a concentration of 1 μM had no effect on HCAECs. Concentrations of 10 μM and 100 μM showed extreme toxicity. Paclitaxel toxicity, even at lower concentrations, was augmented by the addition of hydrogen peroxide and LPS, which simulates conditions occurring with myocardial ischemia. Pretreatment with selenium was effective in decreasing the inflammatory response of HCAECs, measured as less depletion of intracellular GSH and lower levels of TBARS. However, selenium was not effective in preventing paclitaxel-induced apoptosis. Conclusion: Selenium treatment decreases the indirect toxicity of paclitaxel on HCAECs (inflammatory response) but does not prevent the direct toxicity of paclitaxel on HCAECs (apoptosis).